Duodenal perforation caused by deferasirox “case report” - Mohammmed Al Blooshi; Mustafa Hamchou; Ahmed AlSalem (Journal of Pediatric Surgery Case Reports, 2023)
Introduction: Gastrointestinal tract perforations are relatively rare in children. Patients who receive repeated blood transfusions are susceptible to iron overload with its own associated complications. To obviate these complications, iron chelation therapy with deferasirox is the treatment of choice. One of the rare complications of chronic treatment with deferasirox is gastrointestinal perforations. The aim of this report is to outline aspects of diagnosis, management, and the role of minimal invasive surgery in the management of this rare complication. Case presentation: This report describes a case of duodenal perforation in a 5-year-old patient with beta-thalassemia receiving multiple blood transfusions and on chronic chelation with deferasirox. She presented to the emergency department with vomiting and diarrhea of 5 days duration and diagnosed to have acute viral gastroenteritis. She was admitted to the pediatric medical ward and later on the same day she developed severe abdominal pain, mostly in the epigastric region. On physical examination, she was initially afebrile but later developed fever (38.9 °C). She was also tachycardic (a heart rate of 130 beats/min), and tachypneic (a breathing rate of 24–28 breaths per minute). Her blood pressure was 115/76 mmHg. Her abdominal examination revealed generalized abdominal tenderness with guarding and mildly reduced bowel sounds. An erect abdominal x-ray revealed free intraabdominal air which was confirmed by an abdominal CT scan. The diagnosis of gastrointestinal perforation was made, and the patient was prepared for an emergent diagnostic laparoscopy which revealed a duodenal perforation in the anterior aspect of the first part of the duodenum. Primary repair of the perforation was done, followed by reinforcement with a Graham patch and peritoneal lavage. Postoperatively she did well and was discharged home on the 8th postoperative day. Conclusions: Deferasirox induced duodenal perforation is very rare. Duodenal perforation should be suspected in patients with severe gastrointestinal symptoms and abdominal tenderness while on Deferasirox, especially at high doses (30+ mg/kg). Awareness of this rare complication is important to avoid delay in diagnosis and treatment with its known sequalae. Once suspected the diagnosis can be confirmed and managed laparoscopically.